Medieval women, material culture, and power : Matilda Plantagenet and her sisters - Jasperse, Jitske (Gender and power in the premodern world, 2020)
"This book argues that the impressive range of belongings that can be connected to Matilda Plantagenet, duchess of Saxony--textiles, illuminated manuscripts, coins, chronicles, charters, and literary texts--and her sisters allows us to perceive elite women's performance of power, even when they are largely absent from the official documentary account. The material traces connected to Matilda and some of her contemporaries show the importance of women as makers of material culture, as well as the dual agency of women and their objects in the consolidation of their very real, if all but unwritten, power. It is especially through the visual record of material culture that we can hear female voices, showing that women were capable of impacting their own lives as well as that of others, even if charters and chronicles fail to mention so. This forces us to redefine assumptions about power for sparsely-documented noblewomen"--Publisher's description